Exploring the Potential of Metal–Organic Frameworks for the Separation of Blends of Fluorinated Gases with High Global Warming Potential - Sosa, Julio E. (2022)
The authors acknowledge the financial support from the LIFE‐4‐Fgases project, LIFE20 CCM/ES/001748, funded by EU LIFE Programme. the contracts of Individual Call to Scientific Employment Stimulus 2020.00835.CEECIND (J.M.M.A.)/2021.01432.CEECIND (A.B.P.), and the Norma Transitória DL 57/2016 Program Contract (R.P.P.L.R.). Publisher Copyright: © 2022 The Authors. Global Challenges published by Wiley-VCH GmbH.